2021
DOI: 10.1051/parasite/2021037
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and protective efficacy of a new conserved hypothetical protein ofEimeria tenella

Abstract: Eimeria tenella is an obligate intracellular parasite that actively invades cecal epithelial cells of chickens. This parasite encodes a genome of more than 8000 genes. However, more than 70% of the gene models for this species are currently annotated as hypothetical proteins. In this study, a conserved hypothetical protein gene of E. tenella, designated EtCHP18905, was cloned and identified, and its immune protective effects were evaluated. The open reading frame of EtCHP18905 was 1053bp and encoded a protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…One-week-old chickens were weighed and randomly placed into 4 groups, each consisting of 12 birds [ 9 ]. The experimental design of immunizations and challenges is shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…One-week-old chickens were weighed and randomly placed into 4 groups, each consisting of 12 birds [ 9 ]. The experimental design of immunizations and challenges is shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…rEtROP17 was expressed in Escherichia coli BL21 (DE3) and purified using the His60 Ni Gravity Columns (Takara, Dalian, China). Hence, the development of novel control measures such as subunit vaccines has attracted widespread attention [9]. Eimeria tenella is an important species owing to its association with many coccidiosis outbreaks [10].…”
Section: Amplification and Recombinant Expression Of Etrop17mentioning
confidence: 99%
See 2 more Smart Citations
“…They are secreted by microneme organelles that promote adhesion between parasites and the surface of host cells and perform the dynamics required for host cell invasion (Carruthers and Tomley 2008 ). Microneme proteins were found to effectively protect hosts from parasites in Toxoplasma gondii and chicken coccidia (Lee et al 2018 ; Sathish et al 2011 ; Zhao et al 2021a , b ); however, no studies have been reported on rabbit coccidia.…”
Section: Introductionmentioning
confidence: 99%